Essays in Economic Sociology - Weber, Max (Princeton University Press, 2021)
The writings of Max Weber (1864-1920) contain one of the most fascinating and sophisticated attempts ever made to create an economic sociology. Economic sociologist and Weber scholar Richard Swedberg has selected the most important of Weber's enormous body of writings on the topic, making these available for the first time in a single volume. The central themes around which the anthology is organized are modern capitalism and its relationships to politics, to law, and to culture and religion; a special section is devoted to theoretical aspects of economic sociology. Swedberg provides a valuable introduction illuminating biographical and intellectual dimensions of Weber's work in economic sociology, as well as a glossary defining key concepts in Weber's work in the field and a bibliographical guide to this corpus.